Role of corticosteroid Injections versus Physiotherapy for the Treatment of Painful Stiff Shoulder: A Randomised Control Trial - Nahar, Shamsun; Islam, Monirul; Hakim, M Aliha; Ullah, AKM Anwar (Bangladesh Journal of Neuroscience, 2009)
Study Question: among local corticosteroid injections and physiotherapy, which is the more effective treatment for painful stiff shoulder? Objective: To compare the effectiveness of corticosteroid injections with physiotherapy for the treatment of painful stiff shoulder. Design: Randomised trial. Setting: Physical Medicine Outpatient Department (OPD) of BSMMU and NITOR Subjects: Total 119 patients reported to the Outpatient Department (OPD) of NITOR and BSMMU with pain and stiffness in shoulder were enrolled in the trial. Interventions: Patients were randomly allocated to 6 weeks of treatment either with corticosteroid injections (62) or physiotherapy (57). Main outcome measures: Outcome assessments were carried out 3, 7, 13, 26, and 52 weeks after randomisation; some of the assessments were done by an observer blind to treatment allocation. Primary outcome measures were the success of treatment as measured by scores on scales measuring improvement in the main complaint and pain, and improvement in scores on a scale measuring shoulder disability. Results: At 7 weeks 47 (76%) out of 62 patients treated with injections were considered to be treatment successes compared with 26 (45%) out of 57 treated with physiotherapy (difference between groups were 31%, 95% confidence interval 14% to 48%). The difference in improvement favoured those treated with corticosteroids in nearly all outcome measures; these differences were statistically significant. At 26 and 52 weeks differences between the groups were comparatively small. Adverse reactions were generally mild. Conclusions: The beneficial effects of corticosteroid injections administered by the physicians for treatment of painful stiff shoulder are superior to those of physiotherapy. The differences between the intervention groups were mainly the result of the comparatively faster relief of symptoms that occurred in patients treated with injections. Adverse reactions of injections were generally mild. DOI: http://dx.doi.org/10.3329/bjn.v24i1.3034 Bangladesh Journal of Neuroscience 2008; Vol. 24 (1) : 1-8